KILAS BALIK KALENDER HIJRIYAH INDONESIA PERJALANAN MENUJU PENYATUAN KALENDER NASIONAL - Hosen, Hosen (Madura State Islamic Institute (Institut Agama Islam Negeri (IAIN) Madura), 2017)
The discourse of unification of hijri calendar in Indonesia became the topic of discussion which always colored throughout the year. Once the importance of the hijri calendar to unite its determination so that there is not always a difference in its determination, especially related to worship such as the beginning of Ramadlan, Syawwal and Dzulhijjah. It is hoped that with one reference to the hijri calendar, religious worship can run in unity for all Indonesian people identical with the unitary state. The existence of various streams and methods that developed in Indonesia in determining the beginning of the month of hijriyah, themes that are crucial and can not be compromised for the unification of the calendar, as well as efforts that have been made to realize the hijri calendar as a national calendar. The existence of Islamic organizations such as NU and Muhammadiyah turned out to have a greater influence in the system of hijri calendar. The State through the Ministry of Religion can not be a single authority who is entitled to issue a reference hijri calendar that must be obeyed by all Indonesian people.